Wholly aromatic polyamide fiber, sheet made therefrom, speaker diaphragm, and manufacturing method for the same
By employing fully aromatic polyamide fibers with a specific surface area, the challenges of achieving moderate bending strength and cost-effectiveness in speaker diaphragms are addressed, resulting in improved sound quality and moldability.
Patent Information
- Application Number
- JP2023173355
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-05
- Publication Date
- 2025-04-17
AI Technical Summary
Existing technologies face challenges in producing a speaker diaphragm with moderate bending strength while maintaining cost-effectiveness, as high-strength fibers like aramid require high blending percentages due to low binder power, and aramid nanofibers are costly and difficult to produce with sufficient binder force.
The use of fully aromatic polyamide fibers with a specific BET specific surface area, ranging from 30m²/g to 100m²/g, which provides a moderate binder force and is suitable for producing a speaker diaphragm with balanced bending strength and moldability.
This approach allows for the production of a speaker diaphragm with a Galley bending strength of 120 mN to 250 mN, achieving excellent sound quality while maintaining cost-effectiveness and improved moldability.
Smart Images

Figure 2025064003000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to wholly aromatic polyamide fibers, a sheet and a speaker diaphragm made using the same, and a method for producing the same. [Background technology]
[0002] One of the important indicators for products made by molding fibers into sheets, i.e., paper-shaped products, is the binder strength. The binder strength can be said to be the strength of entanglement between fibers, or between fibers and different materials. One indirect indicator of binder strength is the specific surface area of the fiber. The larger the specific surface area of the fiber, the finer the fiber shape is, and the more contact points there are where the fibers entangle each other, so the stronger the binder strength becomes, and for example, it becomes easier to obtain paper or sheet-like products with excellent tensile strength.
[0003] By the way, one example of a product in which fibers are molded into a sheet, that is, a paper-shaped product, is the speaker diaphragm. In general, the characteristics required for a speaker diaphragm include high strength in various respects, high airtightness, high Young's modulus (elastic modulus, rigidity), and large internal loss (tan δ).
[0004] A high Young's modulus is required for speaker diaphragms in order to suppress deformation of the diaphragm. By suppressing deformation of the diaphragm, the longitudinal wave transmission speed in the diaphragm increases, and distortion in the low frequency range is suppressed. Increasing the bending strength (rigidity) of the diaphragm greatly contributes to improving sound quality.
[0005] On the other hand, it is known that there is a practical upper limit to the magnitude of bending strength. For example, a speaker diaphragm with excessive bending strength will cause problems in formability. Speaker diaphragms with a moderate bending strength are required, and the range is, for example, 100 to 250 mN.
[0006] In order to obtain a speaker diaphragm having an appropriate bending strength, the materials and structures of the speaker diaphragm are continuously studied. For example, paper pulp made of cellulose fibers is often used for paper-based speaker diaphragms, but it is known that in order to increase the strength, cellulose fibers are mixed with high-strength, high-elasticity fibers such as aramid fibers to make speaker diaphragms. In doing so, in order to entangle different types of fibers, that is, to strengthen the binder strength, for example, Patent Document 1 uses aramid fibers that have been beaten. However, the aramid fibers obtained by this method have insufficient binder strength, so it is necessary to mix as much as 15% aramid fibers, which is a problem in terms of cost.
[0007] Furthermore, Patent Document 2 uses aramid nanofibers. By using aramid nanofibers, it has been successful in improving sound quality with a compounding rate of only 2%. However, the manufacturing process of aramid nanofibers is complicated, and organic solvents are also used, which means costs are incurred for cleaning to reduce residual solvents, and ultimately the cost issue has not been resolved.
[0008] In addition, although aramid nanofibers maintain a good dispersion state in organic solvents, a separate dispersion treatment is required to improve their dispersibility in water. Depending on the method or extent of this treatment, the dispersion state may deteriorate and the material may not be able to exert sufficient binding power, resulting in a deterioration in sound quality. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2007-208809 A [Patent Document 2] JP 2022-17796 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made to solve the above problems, and an object of the present invention is to obtain a wholly aromatic polyamide fiber having an appropriate binder strength and a speaker diaphragm using the same. [Means for solving the problem]
[0011] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by using wholly aromatic polyamide fibers having a particular specific surface area.
[0012] That is, according to the present invention, 1. A wholly aromatic polyamide fiber having a BET specific surface area of 30 m2 or more measured after drying in an air atmosphere. 2 / g or more 100m 2 / g or less. 2. After alcohol substitution, the BET specific surface area was measured by freeze-drying and was 100 m 2 / g or more 200m 2 2. The wholly aromatic polyamide fiber according to 1 above, wherein the fiber weight is 1 / g or less. 3. The binder strength, defined as the difference between the BET specific surface area measured by drying using the freeze-drying method after alcohol replacement and the BET specific surface area measured after drying in an air atmosphere, is 100m 2 2. The wholly aromatic polyamide fiber according to 1 above, wherein the molecular weight is 1 / g or more. 4. The wholly aromatic polyamide fiber according to 1 above, wherein the wholly aromatic polyamide fiber has a branched structure. 5. The wholly aromatic polyamide fiber according to 1 above, wherein the wholly aromatic polyamide fiber is a hydrous molded product obtained by subjecting a wholly aromatic polyamide polymer solution to a water-based coagulation liquid, and the moisture content of the fiber is 5 to 99%. 6. A sheet using the wholly aromatic polyamide fiber according to 1 above, the sheet containing the wholly aromatic polyamide fiber in an amount of 0.5 to 50.0%. 7. The sheet according to 6 above, wherein the tensile strength of the sheet is 35N or more. 8. A speaker diaphragm using the sheet according to 6 or 7 above. 9. The speaker diaphragm according to 8 above, having a Gurley bending strength of 120 mN or more and 250 mN or less. 10. A method for producing the wholly aromatic polyamide fiber according to 1 above, comprising a step of beating the fiber. Effect of the Invention
[0013] As a result, it is possible to obtain wholly aromatic polyamide fibers having an appropriate binder strength and a speaker diaphragm having an appropriate bending strength. [Brief description of the drawings]
[0014] [Figure 1] 1 shows a typical example of the wholly aromatic polyamide fiber of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] <Fully aromatic polyamide fiber> The wholly aromatic polyamide fiber of the present invention has a BET specific surface area of 30 m2 or more measured after drying in an air atmosphere. 2 / g or more 100m 2 / g or less (preferably 30m 2 / g or more 90m 2 / g or less, more preferably 30m 2 / g or more 80m 2 / g or less, more preferably 30m 2 / g or more 70m 2 If the BET specific surface area measured after drying in an air atmosphere is smaller than the above lower limit, too many wholly aromatic polyamide fibers will be entangled with each other, and the surface area available for entangling with other materials (e.g., cellulose fibers, etc.) will be reduced, resulting in an insufficient ability to hold other materials, which is undesirable.
[0017] In addition, the wholly aromatic polyamide fiber of the present invention preferably has a BET specific surface area of 100 m2 or less, as measured by drying using a freeze-drying method after alcohol substitution.2 / g or more (preferably 100m 2 / g or more 200m 2 / g or less, more preferably 100m 2 / g or more 190m 2 / g or less, particularly preferably 100m 2 / g or more 180m 2 If the BET specific surface area measured by drying using a freeze-drying method after alcohol substitution is smaller than the above lower limit, the surface area available for entangling with other materials (e.g., cellulose fibers, etc.) will be low, and the ability to hold other materials may be insufficient.
[0018] Furthermore, the wholly aromatic polyamide fiber of the present invention preferably has a binder strength of 100 m, which is defined as the difference between the BET specific surface area measured by drying by freeze-drying after alcohol substitution and the BET specific surface area measured after drying in an air atmosphere. 2 / g or more (preferably 100m 2 / g or more 170m 2 / g or less, more preferably 100m 2 / g or more 150m 2 / g or less, particularly preferably 100m 2 / g or more 130m 2 If the binder strength is less than the above lower limit, the specific surface area for entanglement is reduced, and the ability to hold other functional materials may be insufficient.
[0019] Regarding the binder force, when measuring the value of the specific surface area of an object having a fine shape, a method is known in which, particularly for objects dispersed in water, the object is freeze-dried after being replaced with an alcohol-based solvent such as isopropyl alcohol. This is because if water is attached to the surface of an object, when the water starts to evaporate and the droplets become smaller, the object is pulled by the surface tension of the water, which induces aggregation and ultimately becomes an aggregate, making it impossible to measure the original specific surface area. By replacing the water with an alcohol-based solvent such as isopropyl alcohol, the surface tension can be reduced as much as possible, and the aggregation of the object during drying can be suppressed, allowing the original specific surface area of the object to be measured. Considering this principle, the value of the specific surface area measured by drying without replacing the water and the value of the specific surface area measured by drying after replacing the water with alcohol indicate how much the object will aggregate due to drying, that is, they can be said to be an index of the binder force.
[0020] Furthermore, the wholly aromatic polyamide fiber of the present invention may include para-type wholly aromatic polyamides (poly-p-phenylene terephthalamide, poly-p-benzamide, poly-p-amide hydrazide, poly-p-phenylene terephthalamide-3,4-diphenyl ether terephthalamide, etc.), meta-type wholly aromatic polyamides (poly-m-phenylene isophthalamide, etc.), and copolymers of para-type wholly aromatic polyamides and meta-type wholly aromatic polyamides, with para-type wholly aromatic polyamides being preferred because of their high elasticity and strength.
[0021] The wholly aromatic polyamide fiber of the present invention is preferably a fiber having a branched structure. The branched aramid fiber of the present invention is composed of a trunk portion formed by agglomeration of many components, and a branch portion branched from the trunk portion. The branched aramid fiber of the present invention may further have a structure including a portion in which the components are spread flat and arranged in a streamlined manner. Figure 1 shows an example of the fiber of the present invention. Moreover, the wholly aromatic polyamide fiber is preferably produced by a method including a step of beating the fiber.
[0022] <Water-containing molded product> The hydrous molded product in the present invention refers to a thin leaf-like or scale-like piece having fine fibrils, a randomly fibrillated micro short fiber, or a granular particulate material, which is prepared by a method such as mixing an organic polymer solution with a coagulating solution of the polymer solution in a system where shear force is present, as described in WO2004 / 099476A1, JP-B-11851, JP-B-5732, etc. Here, amorphous generally refers to a structure before the formation of a crystal structure based on hydrogen bonds. Furthermore, a hydrous molded product is a product in which water is contained in an amorphous structure. Generally, after coagulation, a polymer is crystallized by drying or stretching, but the crystallization is suppressed by containing a certain amount of water in the coagulated polymer, and therefore the crystallization degree of the hydrous molded product is correlated to a certain degree with the water content. Although it cannot be said in general, it is estimated that the higher the water content, the lower the crystallization degree, and the lower the water content, the higher the crystallization degree. The lower the degree of crystallinity, the more flexible the material is, and the more gripping ability (binder-like properties) it has by entangling with other fiber materials such as aramid nanofibers.
[0023] Furthermore, when the water is removed from the hydrous molding through a drying process or the like, the progress of polymer crystallization makes it difficult for a large amount of water to be present in the polymer again, and as a result, the binder-like properties and high strength expected in the present invention are not exhibited, which is undesirable.
[0024] Furthermore, due to the presence of moisture in the hydrous molded product, crystallization of the polymer is suppressed and the polymer itself is flexible and not very rigid. When a sheet-like product is obtained in this state by papermaking or the like and then dried or hot pressed, water is removed from the hydrous molded product in the sheet-like product, causing the polymer to crystallize, and the polymer deforms smoothly during this process, which is thought to have the effect of giving the resulting sheet high strength.
[0025] From the above, the moisture content of the hydrous molding is preferably 5 to 99%, and if it is less than 5%, the crystallinity will be high and the high strength of the present invention will not be obtained. If it is more than 99%, it is not preferable because it is mostly water and the efficiency will be poor. More preferably, it is 10% or more and 99% or less, and most preferably 20% or more and 99% or less.
[0026] The hydrous molding of the present invention is a wholly aromatic polyamide fiber. Examples of the wholly aromatic polyamide fiber include para-type wholly aromatic polyamide, meta-type wholly aromatic polyamide, and a copolymer of para-type wholly aromatic polyamide and meta-type wholly aromatic polyamide, and para-type wholly aromatic polyamide is preferable because of its high elasticity and high strength.
[0027] The wholly aromatic polyamide used as the raw material for the wholly aromatic polyamide polymer solution for obtaining the hydrous molded product does not have to be a virgin product, and may be, for example, a wholly aromatic polyamide obtained by recycling used products.
[0028] <Sheet> In the present invention, a sheet containing the above-mentioned wholly aromatic polyamide fiber can be formed. Such a sheet has excellent powder shedding resistance (powder shedding prevention), and has good tensile strength and tensile modulus. The tensile strength of the sheet is preferably 35N or more, more preferably 50N or more, and even more preferably 60N or more. There is no particular upper limit, but 100N or less is sufficient. The tensile modulus is preferably 400MPa or more, more preferably 500MPa or more, and even more preferably 550MPa or more. There is no particular upper limit, but 1000MPa or less is sufficient.
[0029] The content (weight %) of the wholly aromatic polyamide fiber in such a sheet is preferably 0.5 to 50.0%.As the other component, it is preferable to use other fiber components such as cellulose fiber.
[0030] <Speaker diaphragm> The speaker diaphragm of the present invention preferably contains cellulose fiber and wholly aromatic polyamide fiber, and more preferably contains 0.1 to 49.9% by weight of wholly aromatic polyamide fiber. In this way, a speaker diaphragm with good sound quality can be obtained in all ranges.
[0031] The content of the aromatic polyamide fiber is preferably 0.1 to 49.9% by weight, more preferably 1.0 to 20.0% by weight, and even more preferably 1.0 to 10.0% by weight. In this way, a speaker diaphragm that is excellent in all ranges can be obtained. If the content of the fine aramid material exceeds 50.0% by weight, the rigidity becomes too high, which is undesirable because it impairs moldability.
[0032] The Gurley bending strength of the speaker diaphragm is preferably 100 mN or more and 250 mN or less, more preferably 120 mN or more and 250 mN or less, even more preferably 120 mN or more and 200 mN or less, and particularly preferably 120 mN or more and 150 mN or less. If the Gurley bending strength is greater than the upper limit, problems arise in formability, which is undesirable. If it is less than the lower limit, the longitudinal wave transmission speed decreases, and distortion in the low-frequency range increases, which is undesirable, and there is a concern that sound quality will deteriorate. EXAMPLES
[0033] The present invention will be described in detail below with reference to examples and comparative examples, but the scope of the present invention is not limited to the following examples and comparative examples. The respective property values in the examples were measured by the following methods.
[0034] <Specific surface area and binder strength> The fully aromatic polyamide fiber was dried in an oven at 120°C under air for 60 minutes to obtain a sample for specific surface area measurement (air atmosphere drying). Separately, the fiber was immersed in isopropanol or t-butyl alcohol, and then freeze-dried to obtain a sample for specific surface area measurement (after alcohol replacement). The specific surface areas of the two samples obtained were measured using a flow-type automatic specific surface area measuring device (Shimadzu Corporation, FlowSorbIII). The binder power was calculated as the difference between the specific surface area value of the freeze-dried sample and the specific surface area value of the sample dried in a 120°C oven.
[0035] <Gurley bending strength (Gurley bending resilience, bending resistance)> The Gurley bending strength was measured in accordance with JIS L 1096:2020 bending resilience A method bending softness.
[0036] <Tensile test> A tensile test was carried out according to the test method of JIS P 8113 (2006) except that the sheet obtained in the present invention was cut into strips with a width of 10 mm. A Tensilon universal material testing machine (RTF series) was used as the tensile tester, and the tensile strength and tensile modulus were measured.
[0037] <Sound quality> The speaker diaphragm was attached to a speaker and listened to. Five randomly selected panelists rated the sound quality from best to worst as "+++", "++", "+", "±", and "-". The rating with the most votes was adopted by majority vote and became the sound quality result for that speaker diaphragm.
[0038] [Example 1] According to the method described in Patent No. 4852328, a hydrous molded product (aramid fibrid) made of para-type fully aromatic polyamide fiber was obtained. Water was added to this hydrous molded product (aramid fibrid) to adjust the concentration to 1% by weight, and the product was defibrated to obtain a hydrous molded product disintegration liquid. This disintegration liquid was beaten with a high-pressure homogenizer (manufactured by COS 21 Co., Ltd., N-2000 110) to obtain a fully aromatic polyamide fiber (fine aramid fibrid). The beating process was performed three times with a clearance of 70 μm and a pressure of 150 MPa.
[0039] [Comparative Example 1] According to the method described in Japanese Patent No. 4852328, a hydrous molded product (aramid fibrid) made of para-type wholly aromatic polyamide fiber was obtained.
[0040] [Comparative Example 2] A microfibrillated aramid fiber, Tiara (registered trademark) KY400S manufactured by Daicel Miraize Co., Ltd. (formerly Daicel FineChem Co., Ltd.), was used.
[0041] [Comparative Example 3] According to the method described in JP 2022-17796 A, aramid nanofibers made of para-type wholly aromatic polyamide fibers were obtained.
[0042] [Table 1]
[0043] [Example 2] A sheet was produced by mixing 2% by weight of the fibers (fine aramid fibrids) obtained in Example 1 and 98% by weight of cellulose fibers by a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd. The tensile strength was higher than that of the sheet described in Comparative Example 7, which was made of cellulose fibers alone. The tensile strength was also higher than that of the sheets described in Comparative Examples 4 and 5. In both cases, it is believed that the fine aramid fibrids obtained in Example 1 tightly bound the fibers in the sheet with their strong binder power.
[0044] [Example 3] A sheet was produced by mixing 20% by weight of the fibers (fine aramid fibrids) obtained in Example 1 and 80% by weight of cellulose fibers by a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd. The tensile strength was higher than that of the sheet described in Comparative Example 7, which was made of cellulose fibers alone. The tensile strength was also higher than that of the sheets described in Comparative Examples 4 and 5. In both cases, it is believed that the fine aramid fibrids obtained in Example 1 tightly bound the fibers in the sheet with their strong binder power.
[0045] [Example 4] A sheet was produced by mixing 50% by weight of the fibers (fine aramid fibrids) obtained in Example 1 and 50% by weight of cellulose fibers by a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd. The tensile strength was higher than that of the sheet described in Comparative Example 7, which was made of cellulose fibers alone. The tensile strength was also higher than that of the sheets described in Comparative Examples 4 and 5. In both cases, it is believed that the fine aramid fibrids obtained in Example 1 tightly bound the fibers in the sheet with their strong binder power.
[0046] [Comparative Example 4] A sheet was produced by mixing 20% by weight of the fiber (aramid fibrid) obtained in Comparative Example 1 and 98% by weight of cellulose fiber by a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd. The tensile strength was lower than that of the sheet described in Comparative Example 7 consisting of only cellulose fiber, which is thought to be due to insufficient binder strength. The tensile strength was also lower than that of the sheets described in Examples 2 to 4. This is thought to be due to insufficient binder strength, which made it difficult to sufficiently bind the fibers in the sheet.
[0047] [Comparative Example 5] A sheet was produced by mixing 2% by weight of Tiara (registered trademark) KY400S, a microfibrillated aramid fiber manufactured by Daicel Miraize Co., Ltd. (formerly Daicel FineChem Co., Ltd.), and 98% by weight of cellulose fiber, using a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd. The tensile strength was lower than that of the sheet described in Comparative Example 7, which is made only of cellulose fiber. The tensile strength was also lower than that of the sheets described in Examples 2 to 4. This is thought to be because the binder force was insufficient and the fibers in the sheet could not be sufficiently bound.
[0048] [Comparative Example 6] A sheet containing 100% by weight of cellulose fiber was produced by a wet papermaking method using a square sheet machine (250 mm square, No. 2555) manufactured by Kumagai Riki Kogyo Co., Ltd.
[0049] [Table 2]
[0050] [Example 5] A sheet was produced by mixing 2% by weight of the fiber (fine aramid fibrid) obtained in Example 1 and 98% by weight of cellulose fiber by a wet papermaking method using a square sheet machine manufactured by Kumagai Riki Kogyo Co., Ltd. This sheet was molded by hot pressing at 140°C to obtain a speaker diaphragm. The obtained speaker diaphragm was subjected to a sensitivity test and evaluated for Gurley bending strength.
[0051] The speaker diaphragm produced in this example exhibited a higher Gurley bending strength and better sound quality than the speaker diaphragms described in Comparative Examples 8, 10, and 14. Compared with the speaker diaphragms described in Comparative Examples 11 and 15, the speaker diaphragm produced in this example exhibited higher sound quality despite the lower amount of aramid material blended. Also, the speaker diaphragm exhibited sound quality equivalent to that of Comparative Examples 12 and 13.
[0052] [Example 6] A speaker diaphragm was obtained in the same manner as in Example 5, except that the fine aramid fibrids obtained in Example 1 were used at 4% by weight and the cellulose fibers were used at 96% by weight. The speaker diaphragm produced in this example exhibited a higher Gurley bending strength and better sound quality than the speaker diaphragms described in Comparative Examples 8, 10, and 14. Compared with the speaker diaphragms described in Comparative Examples 11 and 15, the speaker diaphragm produced in this example exhibited higher sound quality despite the lower amount of aramid material blended. Also, the speaker diaphragm exhibited sound quality equivalent to that of Comparative Examples 12 and 13.
[0053] [Example 7] A speaker diaphragm was obtained in the same manner as in Example 5, except that the fine aramid fibrids obtained in Example 1 were 10% by weight and the cellulose fibers were 90% by weight. The speaker diaphragm produced in this example exhibited a high Gurley bending strength and good sound quality compared to the speaker diaphragms described in Comparative Examples 8, 10, and 14. Compared to the speaker diaphragms described in Comparative Examples 11 and 15, the speaker diaphragm produced in this example exhibited high sound quality despite the low blending amount of aramid material. In addition, the speaker diaphragm showed sound quality equivalent to that of Comparative Examples 12 and 13.
[0054] [Example 8] A loudspeaker diaphragm was obtained in the same manner as in Example 5, except that the fine aramid fibrids obtained in Example 1 were 15% by weight and the cellulose fibers were 85% by weight. The loudspeaker diaphragm produced in this example exhibited a higher Gurley bending strength and a better sound quality than the loudspeaker diaphragms described in Comparative Examples 8, 10, and 14. The sound quality was also equivalent to that of Comparative Examples 12 and 13.
[0055] [Example 9] A loudspeaker diaphragm was obtained in the same manner as in Example 5, except that the fine aramid fibrids obtained in Example 1 were used at 20% by weight and the cellulose fibers were used at 80% by weight. The loudspeaker diaphragm produced in this example exhibited a high Gurley bending strength and good sound quality compared to the loudspeaker diaphragms described in Comparative Examples 8, 10, and 14.
[0056] [Comparative Example 7] A speaker diaphragm was obtained using only cellulose fibers in the same manner as in Example 5. The speaker diaphragm produced in this example had inferior sound quality compared to the speaker diaphragms described in Examples 5 to 9.
[0057] [Comparative Example 8] A speaker diaphragm was obtained using only fully aromatic polyamide fibers (fine aramid fibrids) in the same manner as in Example 5. The speaker diaphragm produced in this example exhibited a high Gurley bending strength exceeding the measurement limit, but molding was difficult, and problems with moldability were identified.
[0058] [Comparative Example 9] A speaker diaphragm was obtained in the same manner as in Example 5, except that the amount of Tiara (registered trademark) KY400S in Comparative Example 2 was 2% by weight and the amount of cellulose fiber was 98% by weight.
[0059] [Comparative Example 10] A speaker diaphragm was obtained in the same manner as in Example 5, except that the amount of Tiara (registered trademark) KY400S in Comparative Example 2 was 15% by weight and the amount of cellulose fiber was 85% by weight.
[0060] [Comparative Example 11] A speaker diaphragm was obtained in the same manner as in Example 5, except that the aramid nanofibers of Comparative Example 3 were 2% by weight and the cellulose fibers were 98% by weight. Although the sound quality was improved compared to Comparative Example 7 by using the aramid nanofibers, the aramid nanofibers may not have been able to exert sufficient binding power due to issues with their dispersibility in water, and as a result, the sound quality was inferior to Examples 5 to 7.
[0061] [Comparative Example 12] A speaker diaphragm was obtained in the same manner as in Example 5, except that the aramid nanofibers of Comparative Example 3 were 15% by weight and the cellulose fibers were 85% by weight. Although the sound quality was improved compared to Comparative Example 7 by using the aramid nanofibers, the aramid nanofibers may not have been able to exert sufficient binding power due to issues with their dispersibility in water, and as a result, the sound quality was inferior to Examples 5 to 7.
[0062] [Comparative Example 13] Water was added to the hydrous molded product (aramid fibrids) of Comparative Example 1 to prepare a 1% by weight mixture, and the mixture was defibrated to obtain a hydrous molded product disintegration liquid. A speaker diaphragm was obtained in the same manner as in Example 5, except that the hydrous molded product (aramid fibrids) disintegration liquid was used to prepare a 2% by weight mixture of aramid fibrids and a 98% by weight mixture of cellulose fiber.
[0063] [Comparative Example 14] Water was added to the hydrous molded product (aramid fibrids) of Comparative Example 1 to prepare a 1% by weight mixture, and the mixture was defibrated to obtain a hydrous molded product disintegration liquid. A speaker diaphragm was obtained in the same manner as in Example 5, except that the hydrous molded product (aramid fibrids) disintegration liquid was used to prepare a 15% by weight mixture of aramid fibrids and 85% by weight mixture of cellulose fiber.
[0064] [Table 3] [Explanation of symbols]
[0065] 1. Fiber 11 Stem part of fiber 12 Branches in the fiber 13 The part of the fiber where the components are arranged in a streamlined manner by spreading the fibers flatly
Claims
1. A wholly aromatic polyamide fiber having a BET specific surface area of 30 m2 measured after drying in an air atmosphere. 2 / g or more 100m 2 / g or less.
2. After alcohol substitution, the BET specific surface area was measured by drying using the freeze-drying method and was 100 m 2 / g or more 200m 2 2. The wholly aromatic polyamide fiber according to claim 1, wherein the molecular weight of the fiber is 1 / g or less.
3. The binder strength, defined as the difference between the BET specific surface area measured after drying by freeze-drying after alcohol substitution and the BET specific surface area measured after drying in an air atmosphere, is 100 m 2 2. The wholly aromatic polyamide fiber according to claim 1, wherein the molecular weight is 1 / g or more.
4. The wholly aromatic polyamide fiber according to claim 1 , wherein the wholly aromatic polyamide fiber has a branched structure.
5. The wholly aromatic polyamide fiber according to claim 1, wherein the wholly aromatic polyamide fiber is a hydrous molded product obtained by a process of introducing a wholly aromatic polyamide polymer solution into a water-based coagulation liquid, and the moisture content of the fiber is 5 to 99%.
6. 2. A sheet using the wholly aromatic polyamide fiber according to claim 1, the sheet containing 0.5 to 50.0% of the wholly aromatic polyamide fiber.
7. The sheet according to claim 6, wherein the sheet has a tensile strength of 35 N or more.
8. A speaker diaphragm using the sheet according to claim 6 or 7.
9. 9. The speaker diaphragm according to claim 8, wherein the Gurley bending strength is 120 mN or more and 250 mN or less.
10. The method for producing the wholly aromatic polyamide fiber according to claim 1 , further comprising a step of beating the fiber.
Citation Information
Patent Citations
Acoustic diaphragm, and manufacturing method thereof
JP2007208809A
Sheet for speaker diaphragm
JP2022017796A